Comparing National Patterns of Medical Specialization: A Contribution to the Theory of Professions - Marian Döhler (Max-Planck-Institut für Gesellschaftsforschung; Max-Planck-Gesellschaft zur Förderung der Wissenschaften e.V., 1992)
Policy-making is often characterized by connected processes of conflict management in organizationally separated, but functionally linked arenas. Such multi-level structures are prone to blockades of decision-making, because boundaries between arenas can reinforce conflicts and rules of interaction can reduce the range of alternative decisions. These problems are structureinduced, their solution requires changes in the organizational framework. Linked arenas are - as a rule - merely loosely-coupled. This is why the fabric of multi-level policy processes can be structured by strategic manipulation. Three strategies of interorganizational management via structural adaptation are discussed. All of them revise conditions of conflict generation and conflict solving and reduce the likelihood of blockades. However, the consequences are ambivalent. As the strategies change power relations in the policy field, they provoke reactions of negatively affected actors, who try to regain influence by establishing secondary informal linkages. As a result, multi-level structures develop multiple connections and network-like relations which interact in a dynamic process of permanent adaptation. – – Politische Prozesse verbinden oft mehrere organisatorisch getrennte, aber funktional zusammenhängende Entscheidungsarenen. Da Grenzen zwischen Arenen zur Konfliktverstärkung beitragen und Interaktionsregeln die Entscheidungsspielräme einengen können, sind solche Mehr-Ebenen-Strukturen für Blockaden der Entscheidungsprozesse anfällig. Diese sind strukturell angelegt und können nur durch Anpassung der organisatorischen Bedingungen bewältigt werden. Das ist möglich, weil Verflechtungen zwischen Entscheidungsarenen meist nur lose verbunden und der strategischen Veränderung zugänglich sind. Drei Strategien des interorganisatorischen Konfliktmanagements durch strukturelle Anpassung werden untersucht. Alle richten sich auf die organisatorischen Konfliktursachen und verringern die Wahrscheinlichkeit von Blockaden. Ihre Wirkung ist allerdings ambivalent. Indem sie Machtverhältnisse verändern, provozieren sie Reaktionen der negativ betroffenen Akteure, die versuchen, Einfluß über sekundäre, informelle Verbindungen zurückzugewinnen. Mehr-Ebenen-Strukturen entwickeln sich daher zu mehrfach verflochtenen, netzwerkartigen Zusammenhängen, in denen unterschiedliche Interaktionsmechanismen in dynamischen Prozessen zusammenspielen und sich ständig an Problementwicklungen anpassen.
Keywords: 300